Preparedness of Teachers to Maintain Discipline in the Absence of Corporal Punishment in Bondo District Kenya - Ajowi, Jack Odongo; Omboto, Christine Juma (Journal of Educational and Social Research, 2013)
Discipline of students is critical to educators, parents, and the society as a whole. Secondary schools in Kenya have experienced problems of student discipline for along time. In the year 2001 alone, after the government had banned the use of corporal punishment in schools, 253 schools all over the country went on strike. Most people attributed the trend of strikes in schools to the ban on corporal punishment. While the schools all over the country were portraying a trend of violence, those in Bondo district in Nyanza province appeared incredibly calm with only one case of student strike reported in five years. The study set to find out how the teacher managed student discipline in public secondary schools in Bondo district. The study used survey research design and targeted 40 public secondary schools. Stratified and simple random sampling techniques were used to select a sample of 3 boys’ schools, 2 girls’ and 8 mixed secondary schools for study. A total of 13 secondary schools were sampled. Saturated sampling was used to select all the 13 head teachers, 13 deputy head teachers and 13 heads of guidance and counseling. 26 classroom teachers were selected by simple random and convenient sampling technique, while the students were stratified per class and then 780 of them were selected based on simple random sampling from forms 2, 3 and 4 classes. Form 1 class did not participate in the study because they had just reported in school. Questionnaires, in-depth interview schedules and school documents on discipline were used to collect data. The face and contents of the instruments were validated by experts in the department of educational management in Maseno University and tried out in 2 secondary schools twice at intervals of two weeks in order to determine their ability to generate accurate data. Data were mainly analyzed using basic descriptive statistics like frequencies and mean. Some data from interview schedules were organized into themes and reported verbatim as they emerged from the field.
Keywords: Teacher; Bondo District; Management; Student Discipline; Public Secondary Schools; Kenya.